AKTIVITAS SIRUP EKSTRAK KULIT BUAH RAMBUTAN (Nephelium lappaceum L.) TERHADAP KADAR KOLESTEROL TOTAL DARAH MENCIT (Mus musculus) - Djajanti, Agust Dwi Djajanti; Ade Shafira (Akademi Farmasi Yamasi Makassar, 2024)
This study aims to determine the “Activity of syrup ekstrak from Rambutan Peel (Nephelium lappaceum L.) on reducing total cholesterol levels in the blood of mice (Mus musculus).” This type of research using the pre and post test method. Induction of hypercholesterolemia was carried out by giving high-fat feed, namely duck egg yolk and butter and PTU inducers which were given every day at relatively the same time for 14 days by oral method. On the 15th day the mice were fasted but still given to drink for the next 3 hours. Cholesterol levels were measured after induction for 14 days (induction cholesterol levels). The mice test animals used were 6 mice (Mus musculus) which were divided into 2 treatment groups. On day 15, groups 1 was treated with gemfibrozil 300 mg as a positive control and group 2 was treated with syrup of rambutan peel extract. After 30 minutes, the mice’s cholesterol levels were meansured. On day 16 they were given the same treatment on day 15 and cholesterol levels were menasured 30 minutes after administration. From the results of the study it was concluded that administration of syrup of rambutan peel extract (Naphaleum lappaeum L.) with a level of 250 mg/ml can reduce total cholesterol levels in the blood of mice with an average decrease of 7% and 11%.